The relationship between the category of informativeness and the mechanisms of subject reference in Belarusian and English interviews - Basovets, Irina M. (Journal of the Belarusian State University. Philology, 2023)
The article examines the inﬂuence of referential mechanisms of subject nominations on the category of informativeness of Belarusian and English interviews. The determinants of information-rich texts are determined. Ways of constructing switch subject reference are established based on the contrasted opinions of specialists versus non-specialists presented in the text. The article shows how the inter-discourse knowledge transfer manifests itself in the result of the style codes mixing by means of linguistic mechanisms of authorisation and deauthorisation.